Preparation Adhesive Material Reinforced of Graphite Particles and Study Electrical and Mechanical and Thermal Properties (Baghdad Science Journal, 2007)
The physical, mechanical, electrical and thermal properties containing (Viscosity, curing, adhesion force, Tensile strength, Lap shear strength, Resistively, Electrical conductivity and flammability) of adhesive material that prepared from Nitrocellulose reinforced with graphite particles and aluminum streat. A comparison is made between the properties of adhesive material with varying percentage of graphite powder (0%, 25%, 30%, 35%, 40%) to find out the effect of reinforcement on the adhesive material. The ability of property an electrical was studied through the measurement of conductivity a function of temperature varying. The results of comparison have clearly shown that the increasing of content of the filler material (graphite weight) after limit ratio determined (32%) in material prepare lead to yielding the (CN) material to concept of granular agglomeration. The mechanical properties decrease when graphite weight ratio increases. Electrical conductivity and flammability increases with graphite weight percentage increases, while the electrical conductivity decreases with increases of temperature. The adherent topography of some physically tested Specimens was studied using optical microscopy.